Detection, isolation, characterization, analytical method development with validation and in-silico analysis of new impurity in rivaroxaban - Manohar Reddy Epuru; Jagadam Saroja; Veera Venkata Nanda Kishore Pilli; Ravinder Reddy Vennapureddy (Future Journal of Pharmaceutical Sciences)
Abstract Background For rivaroxaban (RRBN) to be safe and effective, its quality and impurities need to be evaluated. One new impurity (IMP-20.15/2.57) was found during the analysis of intermediate stage compound of RRBN production. The isolation of IMP-20.15/2.57 was achieved by preparative HPLC, using 10 mM ammonium acetate and acetonitrile (gradient elution mode) as mobile phase. The IMP-20.15/2.57 was elucidated using mass spectrometer, FT-IR and NMR (1H and 13C) techniques. A gradient RP-HPLC method was developed for IMP-20.15/2.57 quantification in RRBN API. The chromatographic separation of IMP-20.15/2.57 was done on a Zorbax Eclipse XDB [C18 3.0 mm × 15 cm, 3.5 µm] column with UV detection programmed at 250 nm. Solution A (methanol and buffer have been blended in a 05:95 v/v ratio) and Solution B (acetonitrile) make up the gradient mobile phase. The three batches of RRBN API were analyzed with the developed gradient RP-HPLC approach for the content of IMP-20.15/2.57. Risk assessment tests for IMP-20.15/2.57 were conducted utilizing in silico programs. Results The IMP-20.15/2.57 was elucidated as 4-(4-(2-hydroxy-3-(2-hydroxy-3-(4-(3-oxomorpholino) phenyl amino) propyl amino) propyl amino) phenyl) morpholin-3-one using mass spectrometer, FT-IR and NMR (1H and 13C) techniques. The novel approach was evaluated in accordance with ICH requirements for linearity (0.2495–1.4971 µg/mL; R2-0.99958), accuracy (109.97–117.71% recovery), precision (0.6015–0.9211%RSD), specificity (996.5 peak purity), robustness (no significant variation in retention time and resolution), and quantification limitations (0.2495 µg/mL). The results were deemed appropriate. It became apparent that the IMP-20.15/2.57 content in three batches of RRBN API were below the quantification limits. The in-silico program suggested that there was certainly no possibility of mutagenicity with IMP-20.15/2.57. Conclusion The present gradient RP-HPLC approach suits best for the IMP-20.15/2.57 quantification in RRBN API and offers more effective ways to guarantee the safety of patients and the quality of RRBN.